Research on the Relevance of University Students’ Sports App Technology Acceptance and Useage Satisfaction - et. al., Qichen Miao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research was to explore the relationship between college students' acceptance and usages satisfaction with sports APP technology. This study was based on 668 college students who participated in the trail running sports APP activities, and used the online questionnaire survey method. This research tool used Sports APP Technology Acceptance Scale and Usage Satisfaction Scale. Reliability analysis showed that Cronbach’s α were a value of 0.97 and 0.98. Data analysis used SPSS software for analysis. The results of this study were as follows: 1. College students of different genders had significant differences in the acceptance of science and technology and the degree of satisfaction in usages; 2. "Perceived usefulness" and "perceived ease of use" had a moderately positive correlation with continued use intention; 3. There was a moderately significant positive correlation between the acceptance of science and technology and the degree of satisfaction. The conclusion of this study pointed out that the acceptance and satisfaction of college students for sports APP technology were high, and this result also took advantages of physical exercise in physical education class.